PENGARUH DANA PIHAK KETIGA (DPK), NON PERFORMING FINANCE (NPF), DAN PENDAPATAN MARGIN MURABAHAH TERHADAP PEMBIAYAAN MURABAHAH PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2015-2019 - Anada Nur Afni; Syapsan Syapsan; Widayatsari Any i (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to examine the effect of DPK, NPF, and Murabahah Margin Income on Murabahah Financing at Islamic Commercial Banks in Indonesia. This study uses secondary data, data on third-party funds (dpk), non-performing finance (npf), and murabahah margin income from the data published in Islamic banking financial statements. The data analysis method used the panel data regression equation, using the e-views 10 program facility. This model has also been through a series of classical assumption tests (Multicollinearity and Heteroscedasticity). The results of this study showed that TPF, NPF, and Murabahah margin income have an effect on Murabahah Financing at Islamic Commercial Banks in Indonesia. Partially, TPF has a positive and insignificant effect on Murabahah Financing at Islamic Commercial Banks in Indonesia. NPF has a negative and insignificant effect on Murabahah Financing at Islamic Commercial Banks in Indonesia. Meanwhile, Murabahah Margin Income has a positive and significant effect on Murabahah Financing at Islamic Commercial Banks in Indonesia. The value of R2 shows the number 0.986, which means that the relationship between the independent and dependent variables can be explained by 98%. The remaining 2% is influenced by other variables outside of this study.Keywords: Murabahah Financing, Third Party Funds (DPK), Non-Performing Finance (NPF), Murabahah Margin Income.